Problematika Pendidikan Anak Pasca Perceraian Orangtua - Despi Trianti; Nuzuar Nuzuar; Siswanto Siswanto; Idi Warsah; Endang Endang (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
Children are the mandate from Allah in that children have the rights to live and be loved by parents. Children’s growth and development are very dependent upon how parents educate and guide them. Children are like white paper given the potential by Allah, and such potential must be developed by parents in any condition and situation even though, for instance in a particular case, the parents must get divorce. Departing from this argument, this study aimed to find out a depiction of children's (17 children) education continuity after their parents got divorce in Babakan Baru Village, Bermani Ulu Raya District, Rejang Lebong Regency, Bengkulu. This study used a qualitative approach with key informants referring to parents who got divorce, close family members, child victims of divorce, and community and religious leaders. In addition, the marriage registrars of KUA in Bernani Ulu Raya were involved as the secondary informants. The data were obtained from observations and interviews, and they were analyzed using the approach of Miles et al with the stages encompassing data reduction, data presentation, and drawing conclusion. This study found the conclusion that the continuity of children's education after parental divorce in Babakan Baru Village was not solely grounded in parental divorce, but it was more dominantly influenced by economic factors and parents' awareness of the importance of children’s education.